Stability analysis of fat and polyphenol content of five cocoa clones grown in different environment in Indonesia. - Al-Afandi, Muhammad; Anita Sari, Indah; Wahyu Susilo, Agung; Widura Ritonga, Arya; Setyawan, Bayu; Malik, Abdul (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Fat and polyphenols are functional compounds in cocoa beans that determine product quality and are highly influenced by environmental factors. Informationregarding the stability of the character of the polyphenol and fat content of the cocoa plant is still limited, therefore it needs further study. This study aimed todetermine the stability of fat and polyphenol content in several cocoa clones at three different growing locations. The study used a nested design with a randomized block design with field design consisting of five cocoa clones, three different growing locations and each combnation treatment was repeated three times. The cocoa clones used were ICCRI 09, MCC 02, Sulawesi 1, KW 516, and KW 562, planted in three different growing locations namely, Kaliwining Experimental Station, Jember, East Java; Sekampung Udik, East Lampung, Lampung; and Harapan Jaya, Pesawaran, Lampung. The combined analysis of variance indicated that there was a genetic interaction with the environment for the character of fat and polyphenol content. Based on the stability analysis, it is known that all cocoa clones fall into the stable category according to the concept of static stability. Furthermore, based on addtive main effect and multiplicative interaction (AMMI) analysis, the clones that can be recommended for Jember, East Lampung and Pesawaran locations for the character of fat content are clone KW 516, while for the characters of high and stable polyphenol levels at the three locations are clones MCC 02, KW 516, and KW 562. In addition, the most recommended clone based on fat content at Jember was the MCC 02 clone, KW 562 at East Lampung, and KW 516 clone at Pesawaran. The existence of the phenomenon of genetic interaction and the growing environment for the characters of fat and polyphenols in cocoa plants provides important information, especially in considering the development of cocoa for specific purposes, namely parameters of fat and polyphenols.